2021
DOI: 10.1111/jcmm.15844
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb3 alleviates smoke‐induced lung injury via the H19/miR‐29b‐3p/HGMB1/TLR4 signalling pathway

Abstract: The over‐activation of inflammation is involved in the pathogenesis of smoke‐induced lung injury (SILI), while Rb3 treatment may alleviate smoke‐induced lung injury by down‐regulating the expression of H19, a regulator of miR‐29b expression. Moreover, HMGB1 is an important mediator of inflammation. Therefore, in this study, we set up an animal model of SILI and treated it with Rb3 to study the effect of Rb3 on the treatment of SILI and the involvement of H19/miR‐29b/HMGB1/TLR4 signalling. SILI mice treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It is not difficult to see from the table that there are currently three drugs targeting H19 to treat lung diseases, namely melatonin, Curcumenol and Ginsenoside Rb3. Both Curcumenol and Ginsenoside Rb3 inhibit H19 expression through the H19/miR-19b-3p/ FTH1 axis and the H19/miR-29b-3p/HGMB1/TLR4 axis to promote ferroptosis in lung cancer cells and reduce inflammation (Tan et al, 2021;Zhang et al, 2022). But Wang showed that melatonin upregulated H19 expression to suppress PAH, in contrast to other reports that H19 promoted this disease (Wang et al, 2018a).…”
Section: The Drugs Targeting H19mentioning
confidence: 88%
See 2 more Smart Citations
“…It is not difficult to see from the table that there are currently three drugs targeting H19 to treat lung diseases, namely melatonin, Curcumenol and Ginsenoside Rb3. Both Curcumenol and Ginsenoside Rb3 inhibit H19 expression through the H19/miR-19b-3p/ FTH1 axis and the H19/miR-29b-3p/HGMB1/TLR4 axis to promote ferroptosis in lung cancer cells and reduce inflammation (Tan et al, 2021;Zhang et al, 2022). But Wang showed that melatonin upregulated H19 expression to suppress PAH, in contrast to other reports that H19 promoted this disease (Wang et al, 2018a).…”
Section: The Drugs Targeting H19mentioning
confidence: 88%
“…H19 acts as a sponge for miR-29b-3p to regulate its expression negatively. In addition, miR-29b-3p inhibited the expression of toll-like receptor 4 (TLR4) and alleviated lung injury by inhibiting the expression of HMGB1 mRNA (Tan et al, 2021). TLR4 promoted the production of inflammatory mediators (Yang et al, 2020).…”
Section: Lung Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Our result showed that the lncRNAs, participating in the pulmonary inflammation and apoptosis [ 39 , 40 ], were also the RC decoction target genes. The Renshen was reported to regulate the lncRNA levels: the ginsenoside Rb3 increased the lncRNA H19 level and alleviated the smoke-induced lung injury [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ginsenoside Rb3 can regulate H19, 16 indicating that ginsenoside Rd can inhibit tongue cancer by regulating H19. Noncoding RNA H19 is highly expressed in various cancers.…”
Section: Introductionmentioning
confidence: 99%